Kesadaran Teologis Masyarakat Cikadut dalam Menghadapi Pandemi Covid-19 - Sulthan Faiz Khalil Gibran (Jurnal Penelitian Ilmu Ushuluddin, 2022)
The Covid-19 pandemic has melted all aspects of life, whether social, economic, educational, political and so on, religion has become the highest theological awareness for humans to get closer to the creator. Therefore, the purpose of this research is to answer some of the main issues that are the subject of discussion, about how is the theological awareness of the Cikadut community in dealing with Covid-19? This research is a field research, with qualitative methods as a data collection technique and Islamic theology as a knife of analysis. The results of this study indicate that the Cikadut community has various views in responding to the Covid-19 disaster, some believe it and vice versa. There are various ways that the Cikadut community uses to get out of the problem. Among them is theological awareness, in which humans surrender themselves to return everything that exists in this life to God who is omnipotent. And then make every effort to avoid provisions that are deemed unsuitable for life.